Strategi Penguatan Branding dan Implementasi Pembukuan Sederhana pada UMKM Warung Makan Mbak Sari - Putri Setyawan, Maulita; Wulandari Hamzah, Sri; Reza Maulana, Ananda; Suryandani, Wulan (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting local economic development, yet many micro-entrepreneurs still struggle to establish a strong business identity and manage their finances in a structured manner. This community service program aims to enhance the managerial capacity of the MSME “Warung Makan Mbak Sari” through strengthened branding, improved digital visibility, and the implementation of simple bookkeeping practices. The program was conducted using a participatory approach consisting of a pre-survey, program design, hands-on mentoring, and evaluation. The results show that the MSME successfully developed a new visual identity including a logo, banner, and standardized menu which improved recognition and customer appeal. The business was also registered on Google Maps, making it easier for customers to locate the stall and expanding its marketing reach. In financial management, training on simple bookkeeping enabled the owner to record daily income and expenses more accurately and understand basic cashflow conditions. This intervention increased the owner’s confidence and professional capability in managing the business. Overall, the program positively contributed to enhancing the MSME’s operational readiness and competitiveness. The results suggest that practical and targeted assistance can serve as an effective model for other micro-enterprises facing similar challenges. Continued application of improved branding and bookkeeping practices is expected to support sustainable business growth in the digital era.